Teacher training for sexuality education and discourses of gender, sexuality and power - Chaskalson, Julia Lazar (My University, 2020)
This research report is concerned with how teachers are trained to deliver sexuality education in South African schools. Situated in a rich body of literature which demonstrates the importance of school-based sexuality education to several important sexual health and social outcomes, this research report centres the voices of teachers undergoing in-service training for Life Orientation (LO) and argues that teachers are key to furthering adolescent sexual and reproductive health. It takes a Foucauldian approach to the process of teacher-training. Research was conducted at Rhodes University, where focus groups were conducted with fifteen practising LO teachers enrolled in in-service training. Focus groups illuminated teachers’ existing attitudes towards and challenges with sexuality education. I examined the teachers’ hegemonic constructions of gender, sexuality and power, which illustrated deep-seated ‘cultural’ investments to heteropatriarchal power-relations. The research report then turned to state discourses regarding sexuality education, undertaking a textual analysis of the state’s newly released Scripted Lesson Plans (SLPs) for sexuality education. I explored the pertinence of the new SLPs for future teacher-training. The SLPs precipitated a widespread moral panic about sexuality education. I examined the widespread social conservativism which caused the backlash to the SLPs, and argue for a conscientization process –centred around teachers –to ensure ownership and understanding of their material. Overall, it is argued that LO teachers –and the process by which they are trained for their role –are neglected, and effort must be made to support LO teachers while challenging hegemonic discourses pertaining to gender, sexuality and power
Research report submitted to the Faculty of Humanities in partial fulfilment of the requirements for the Master of Arts (MA) Degree in Development Studies, University of the Witwatersrand, School of Social Sciences, 2020
Keywords: Sex instruction; Sex instruction for children--South Africa